MUSLIMAH COSMOPOLITAN LIFESTYLE: ANTARA SYARI’AT, TREND MASA KINI DAN KAPITALISASI AGAMA (Studi Budaya Pop Terhadap Pemilihan Putri Muslimah Indonesia) - Ulya, Inayatul (Palita: Journal of Social Religion Research, 2018)
This article analyzes the importance of the use of popular culture as a method in the study of Islam within the cosmopolitan muslimah lifestyle phenomenon, particullary in the contes of  Putri Muslimah Indonesia (Miss Muslimah Indonesia). The use of popular culture method to understand the real intension of hijab observerance;wether for the purpose observing sharia or just follow the present trend, or religious capitalisation. The Observerance of sharia commonly interpreted by wearing of the so-called sharia clothing. Because wearing sharia  clothing (hijab syar’i) as the symbol of religious piety and secondly, emphasizing that sharia in this case  always adaptive in any circumstances as long as it doesn’t violate the basic teaching of sharia, as the present demand of muslimah lifestyle is expressed in various way, one of them is the trend of hijab syar’i. Third, the utilization of religious symbol to generate economic profit. Various events such as the contes of  Putri Muslimah Indonesia (Miss Muslimah Indonesia) as important booster for muslim fashion industries to gain huge profits by targeting large market of stylist cosmopolitan muslimah. Thus, the element of religious capitalization is much more visible than spreading the true spirit of Islamic teaching.